Assessment of the Effect of Autograft Orientation on Peripheral Nerve Regeneration Using Diffusion Tensor Imaging. Issue 4 (April 2018) - Afshari, Ashkan; Nguyen, Lyly; Kelm, Nathaniel D.; Kim, Justine S.; Cardwell, Nancy L.; Pollins, Alonda C.; Bamba, Ravinder; Shack, R. Bruce; Does, Mark D.; Thayer, Wesley P.
Abstract : Purpose: Given no definite consensus on the accepted autograft orientation during peripheral nerve injury repair, we compare outcomes between reverse and normally oriented autografts using an advanced magnetic resonance imaging technique, diffusion tensor imaging. Methods: Thirty-six female Sprague-Dawley rats were divided into 3 groups: sham—left sciatic nerve isolation without injury, reverse autograft—10-mm cut left sciatic nerve segment reoriented 180° and used to coapt the proximal and distal stumps, or normally oriented autograft—10-mm cut nerve segment kept in its normal orientation for coaptation. Animals underwent sciatic functional index and foot fault behavior studies at 72 hours, and then weekly. At 6 weeks, axons proximal, within, and distal to the autograft were evaluated using diffusion tensor imaging and choline acetyltransferase motor staining for immunohistochemistry. Toluidine blue staining of 1-μm sections was used to assess axon count, density, and diameter. Bilateral gastrocnemius/soleus muscle weights were compared to obtain a net wet weight. Comparison of the groups was performed using Mann-Whiney U or Kruskal-Wallis H tests to determine significance. Results: Diffusion tensor imaging findings including fractional anisotropy, radial diffusivity, and axial diffusivity were similar between reverse and normally oriented autografts. Diffusion tensor imaging tractography demonstrated proximodistal nerve regeneration in both autograft groups. Motor axon counts proximal, within, and distal to the autografts were similar. Likewise, axon count, density, and diameter were similar between the autograft groups. Muscle net weight at 6 weeks and behavioral outcomes (sciatic functional index and foot fault) at any tested time point were also similar between reverse and normally oriented autografts. Conclusions: Diffusion tensor imaging may be a useful assessment tool for peripheral nerve regeneration. Reversing nerve autograft polarity did not demonstrate to have an influence on functional or regenerative outcomes.